2008
DOI: 10.1136/bjo.2008.141903
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of intravitreal and periocular triamcinolone associated with photodynamic therapy for treatment of retinal angiomatous proliferation

Abstract: Combined PDT-IT may offer better results than PDT monotherapy or PDT-PT in patients with RAP stage III.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 29 publications
0
12
0
Order By: Relevance
“…24,25 Combined therapies may offer better results, especially in case of PDT combined with intravitreal triamcinolone. 26 Finally, the size of our series was limited to 29 eyes of 26 patients. However, the follow-up in this series is one of the longest (12 months) and all eyes were treatment naive.…”
Section: Discussionmentioning
confidence: 99%
“…24,25 Combined therapies may offer better results, especially in case of PDT combined with intravitreal triamcinolone. 26 Finally, the size of our series was limited to 29 eyes of 26 patients. However, the follow-up in this series is one of the longest (12 months) and all eyes were treatment naive.…”
Section: Discussionmentioning
confidence: 99%
“…However, a higher rate of complications and RAP recurrences was seen in group 3 [109]. Because of the limited effects of antiangiogenic drugs on stage III lesions [56,106,107] and the longer effect of intravitreal steroids in association with PDT, many authors consider that PDT plus IVTA still plays an important role in the treatment of advanced forms of RAP [107]. Another possible treatment for RAP may be a triple therapy with an anti-VEGF agent, PDT, and steroids.…”
Section: Ivta In Retinal Angiomatous Prolife-ration Therapymentioning
confidence: 93%
“…The concentration level that this dose could reach in the subretinal space is still unclear, and there is no substantial agreement between the physicians, about the optimal dose to be injected in the human eye. Some authors reported good results even with lower doses of TA (2 mg-Iwama D 2008) [42] [55][56][57][58][59] with fewer side effects like cataract and glaucoma. Nevertheless, in most trials the effect of TA was transient.…”
Section: Dosagementioning
confidence: 95%
See 2 more Smart Citations